Supplementation with the histone deacetylase inhibitor trichostatin A during in vitro culture of bovine embryos - Oliveira, Clara Slade [UNESP]; Saraiva, Naiara Zoccal [UNESP]; De Souza, Marcela Maria [UNESP]; De Almeida Drummond Tetzner, Tatiane [UNESP]; De Lima, Marina Ragagnin [UNESP]; Garcia, Joaquim Mansano [UNESP] (Cambridge University Press (CUP), 2013)
Summary Trichostatin A (TSA) is a histone deacetylase inhibitor that induces histone hyperacetylation and increases gene expression levels. The aim of the present study was to establish a suitable condition for the use of TSA in in vitro cultures of bovine embryos, and to determine whether TSA would increase blastocyst rates by improvement of chromatin remodelling during embryonic genome activation and by increasing the expression of crucial genes during early development. To test this hypothesis, 8-cell embryos were exposed to four concentrations of TSA for different periods of time to establish adequate protocols. In a second experiment, three experimental groups were selected for the evaluation of embryo quality based on the following parameters: apoptosis, total cell number and blastocyst hatching. TSA promoted embryonic arrest and degeneration at concentrations of 15, 25 and 50 nM. All treated groups presented lower blastocyst rates. Exposure of embryos to 5 nM for 144 h and to 15 nM for 48 h decreased blastocyst hatching. However, the terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling assay (TUNEL) assay revealed similar apoptosis rates and total cell numbers in all groups studied. Although, in the present study, TSA treatment did not improve the parameters studied, the results provided background information on TSA supplementation during in vitro culture of bovine embryos and showed that embryo quality was apparently not affected, despite a decrease in blastocyst rate after exposure to TSA. © Cambridge University Press 2011.
Keywords: Cattle; Embryonic development; Histone deacetylase inhibition; Histone hyperacetylation; Trichostatin A; histone deacetylase inhibitor; hydroxamic acid; trichostatin A; animal; animal embryo; apoptosis; blastocyst; cattle; chromatin assembly and disassembly; cytology; dose response; drug effect; embryo culture; female; fertilization in vitro; gene expression regulation; male; physiology; prenatal development; Animals; Apoptosis; Blastocyst; Chromatin Assembly and Disassembly; Dose-Response Relationship, Drug; Embryo Culture Techniques; Embryo, Mammalian; Female; Fertilization in Vitro; Gene Expression Regulation, Developmental; Histone Deacetylase Inhibitors; Hydroxamic Acids; Male; Bos; Bovinae